CLTS education: An effective solution for diarrhea prevention in Pejuang, Bekasi - Kusumaningtiar, Devi Angeliana; Anggara, Taufik Rendi; Azteria, Veza; Swamilaksita, Prita Dhyani; ‘Amiroh, Ayu Nadiyah; Andarwulan, Ade Ayu; Putri, Assyifa Ananda; Aljunita, Intan; Iswidiyaningrum, Preeti (Universitas Muhammadiyah Magelang, 2025)
Poor sanitation practices, particularly open defecation, are major contributors to diarrhea, leading to millions of deaths worldwide. In Indonesia, this issue is exacerbated during the dry season. To address this problem, this activity aimed to provide education on diarrhea using a Community-Led Total Sanitation (CLTS) approach. Activities included education on the pillars of CLTS, interactive discussions, and evaluation. Evaluation results demonstrated that CLTS education was effective in increasing community knowledge about diarrhea prevention, indicated by an improvement in average knowledge scores after the intervention. Therefore, widespread dissemination of CLTS through counseling, promotional media, and the involvement of community leaders is highly recommended to improve sanitation quality and prevent diarrhea.